SYSTEMIC OSTEOPOROSIS AND PSORIATIC ARTHRITIS: CURRENT UNDERSTANDING OF THE PROBLEM - O. V. Dobrovolskaya; N. V. Toroptsova; E. Yu. Loginova; T. V. Korotaeva (Научно-практическая ревматология)
The review deals with the problem of generalized osteoporosis (OP) in psoriatic arthritis (PsA). Works published in the past 15 years were sought in the Medline using the keywords «psoriatic arthritis», «osteoporosis», and «osteoporosisassociated fractures» (fragility fractures, low-energy fractures, and osteoporotic fractures). The paper includes the data of studies on the frequency of OP and fractures, the risk factors of OP, and the impact of drug therapy on bone status in patients with PsA.